Serotonin differentially affects morph-specific behavior in divergent populations of a horned beetle. (29th November 2019) - Newsom, Keeley D; Moczek, Armin P; Schwab, Daniel B
Abstract: Associations between animal weapons and corresponding aggressive behaviors are among the most characteristic features of species, yet at the same time their co-expression is itself often strongly dependent on context, such as male condition or population ecology. Yet the mechanisms that modulate associations between aggression, morphology, and biological context remain poorly understood. The biogenic amine serotonin has been shown to regulate a wide range of aggressive and morph-specific behaviors in diverse insect species. However, the extent to which serotonin may coordinate the expression of behavior with morphology across biological contexts remains unclear. In this study, we pharmacologically increased serotonin biosynthesis in males of the polyphenic beetle, Onthophagus taurus, and assessed how this manipulation affects both aggressive and non-aggressive behaviors in alternative fighter and sneaker morphs, as well as in males derived from two rapidly diverging populations characterized by disparate levels of competition for mates. We find (i) that enhancing serotonin biosynthesis increases most measures of aggressive behaviors, but influences only a subset of nonaggressive behaviors, (ii) that similar serotonin-mediated behavioral changes manifest in both morphs within populations more often than just a single morph, and (iii) that males derived from the two focal populations have diverged in their behavioral responsiveness to serotonin up-regulation. Collectively, our study suggests that serotonin signaling plays a critical role in the regulation of male behavior and its evolution, including in the context of rapid, short-term population divergence. Abstract : Animal weapons and aggressive behaviors function and evolve in tight association. Yet, the physiological mechanisms linking morphology and behavior remain poorly understood. We demonstrate that experimental manipulation of serotonin signaling enhances aggression in a species of horned beetles, and that the nature and strength of this effect has diverged heritably among isolated populations subject to strikingly different levels of competition.